A qualitative investigation of the impact of peer to peer online support for women living with Polycystic Ovary Syndrome - Holbrey, Sarah; Coulson, Neil S. (BioMed Central, 2013)
Background: Polycystic Ovary Syndrome is a common, chronic condition which affects women living with the condition both physically and psychologically. Social support may be beneficial to sufferers in coping with chronic conditions and the Internet is becoming a common place for accessing social support and information. The aim of this study was to consider the experiences of women living with Polycystic Ovary Syndrome who access and participate in an online support group discussion forum dedicated to issues surrounding this condition.